Psychosocial Processes and Sexual Initiation Among Ghanaian Youth - McQuestion, M.; Ahiadeke, C.; Posner, J.; Williams, T. (Health Education and Behavior, 2012)
This study models primary abstinence and age at first sex in a cross-sectional sample of Ghanaian youth aged 17 to 22 years. The aim is to examine how reproductive knowledge and social cognitive factors jointly affect the choice to initiate sex. Among males, the authors find that reproductive knowledge is negatively associated with abstinence. Its negative association, however, is moderated by the extent of adult support a respondent receives. Among females, reproductive knowledge is positively associated with abstinence. Its positive association is moderated by the extent of household sex communication. Correspondingly, when age at first sex is modeled, knowledge is a negative predictor among females. Its effects are mediated by household sex communication. A third social cognitive variable, perceived permissive peer attitudes about sex, is not associated with knowledge but is a protective factor for sexual initiation for both sexes. Though causal direction cannot be established, the results suggest that cognition affects sexual initiation both directly and through complex social mechanisms. The evidence provides theoretical support for comprehensive adolescent sexual and reproductive health interventions that promote abstinence and other safe sex behaviors through social as well as individual pathways. © 2012 Society for Public Health Education.
Keywords: adolescents; sex behavior; social cognitive theory; social determinants